1991
DOI: 10.1111/j.1365-2044.1991.tb09665.x
|View full text |Cite
|
Sign up to set email alerts
|

Extradural vein puncture—an avoidable complication

Abstract: SummaryAccidental cannulation of an extradural vein is a troublesome and potentially serious complication of extradural catheter insertion. This study was conducted to assess the influence of posture, catheter size and the injection of saline before catheter insertion, on its occurrence. Eight different techniques were studied based on combinations of these three factors. There was no difference in incidence with respect to posture. The use of 18‐gauge catheters, after injection of 10 ml of 0.9% saline, result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 8 publications
1
11
0
Order By: Relevance
“…Injection of fluid through the epidural needle may facilitate insertion of the epidural catheter [8] and decrease the frequency of blood vessel trauma [8][9][10][11]. This technique was first suggested by Bromage [12], and its efficacy was confirmed by Verniquet [9] and Mannion et al [10].…”
Section: Discussionmentioning
confidence: 95%
“…Injection of fluid through the epidural needle may facilitate insertion of the epidural catheter [8] and decrease the frequency of blood vessel trauma [8][9][10][11]. This technique was first suggested by Bromage [12], and its efficacy was confirmed by Verniquet [9] and Mannion et al [10].…”
Section: Discussionmentioning
confidence: 95%
“…(5) Gadalla et al (6) Mannion et al, (7) all noted a significant reduction in the incidence of extradural vein cannulation by routinely injecting 10 mL of saline priming fluid into the epidural space before catheter insertion. Saline, however, dilutes the local anesthetic injected; in this study, we therefore administered a single-injection dose of local anesthetic (20mL) as a priming solution as done by Cesur et al (5) This study also demonstrated improved surgical conditions with the administration of a single-injection dose through an epidural needle before epidural catheter placement.…”
Section: Discussionmentioning
confidence: 99%
“…(5)(6)(7) Some studies contradicted, (8,9) but in studies showing a lack of effect, either a small and possibly inadequate volume of local anesthetic or normal saline, which would dilute local anesthetic subsequently injected, was given. The use of a large priming dose of local anesthetic has not been studied.…”
mentioning
confidence: 99%
“…Although not all investigators have found a difference between the lateral and the sitting position, 1,12 others have found that epidural vein puncture occurs less frequently in the lateral position. 13,14 Although venous puncture may be more common with the sitting position, there are other effective and readily available strategies to prevent venous cannulation including saline distension of the epidural space before threading the catheter, 12 and the use of flexible spiral wound epidural catheters. 15 …”
Section: Incidence Of Epidural Vein Puncturementioning
confidence: 99%